ANALISIS BUKU TEKS PELAJARAN IPA SMP KELAS VII PADA BUKU ERLANGGA DAN SOAL LATIHAN ULANGAN BERDASARKAN LITERASI SAINS - Erida, Zulfa; Natalina, Mariani; Darmadi, Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to describe the science literacy of science textbooks for junior high school grade VII based on 4 dimensions, namely science as the body of knowledge, scienceas a way of thinking, science as a way of investigation and science and its interaction with technology and society and describe scientific literacy in practice questions the repetition on the seventh grade science book of SMP based on the 2015 PISA framework is competency and knowledge aspects. This research uses a qualitative approach with a content analysis method. The subject of this research is the science textbook class VII published by Erlangga Curriculum 2013. The research data obtained from the results of scientific literacy analysis of books using scientific literacy level analysis instruments based on 4 dimensions of scientific literacy and scientific literacy about repetition exercises using scientific literacy analysis sheet instruments based on 2 aspects of the PISA 2015 framework. Data analysis uses descriptive statistical methods. The results of data analysis showed that scientific literacy in the category of science as an investigation has the highest percentage with a score of 45.48%. The results of the scientific literacy analysis data in the multiple choice test questions show that the aspect of knowledge has a higher percentage than the competency aspect of 86.44% with very good criteria. Whereas the results of the retrial essay practice questions have a higher percentage of 61% with good criteria.KeyWords: Science Literacy, PISA 2015 Framework, Natural Science textbooks for Junior High School, Test questions on tests